Performances of Six-leg DSTATCOM Topology under Various SRF Algorithms - Kumar, Pradeep (International Journal of Integrated Engineering, 2020)
Six-leg DSTATCOM can be employed for improving the superiority of power in a distribution system. DSTATCOM is the most valuable current harmonic reduction device because of its excellent compliance in active situations. The DSTATCOM has a shunt voltage source inverter (VSI) attached to the common coupling point of power system via the interfacing inductor. In its controllers, the various SRF algorithms such as Conventional SRF, DCC based SRF and ICC based SRF have been adopted due to its easy execution aspects. These algorithms create balanced and sinusoidal supply current, compensate the reactive power, improving the power factor near unity on common coupling point and mitigate harmonic in the supply current. The reference signal for PWM generator is generated using SRF algorithms. A 3-phase 4-wire power system with rectified RC/RL load has been taken for the detailed simulation study. The performances of DSTATCOM topology have been compared under conventional SRF, DCC based SRF and ICC based SRF control strategies in terms of power quality improvement.